2003
DOI: 10.1111/j.1939-1676.2003.tb02450.x
|View full text |Cite
|
Sign up to set email alerts
|

A Scoring Index for Disease Activity in Canine Inflammatory Bowel Disease

Abstract: The clinical course of inflammatory bowel disease (IBD) in dogs is characterized by spontaneous exacerbations and remissions, which makes assessment of disease burden difficult. The objectives of this study were to develop a scoring system for evaluation of canine IBD activity and to validate this scoring method by correlating it to objective laboratory and histologic indices of intestinal inflammation. Fifty-eight dogs with IBD were evaluated prospectively and compared to 9 disease-free control dogs. Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
452
5
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(500 citation statements)
references
References 42 publications
(47 reference statements)
23
452
5
11
Order By: Relevance
“…We observed increased CRP concentrations in all the IPA dogs included in this study. This finding was expected based on previous studies that reported elevated CRP concentrations in dogs with other inflammatory diseases [10,12,13,18]. However, all the IPA dogs showed remarkable increase in the CRP levels; these levels in 11 dogs (29%) were greater than the measurement limit.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We observed increased CRP concentrations in all the IPA dogs included in this study. This finding was expected based on previous studies that reported elevated CRP concentrations in dogs with other inflammatory diseases [10,12,13,18]. However, all the IPA dogs showed remarkable increase in the CRP levels; these levels in 11 dogs (29%) were greater than the measurement limit.…”
Section: Discussionsupporting
confidence: 83%
“…CRP has also been used as a predictor of survival in some neoplastic conditions [17] and of risk for myocardial infarction and stroke [6,20]. Recently, the CRP concentration was measured in dogs and it was shown to be elevated in several conditions such as surgical trauma [13], inflammatory bowel diseases (IBD) [12], pancreatitis [10], and autoimmune hemolytic anemia (AIHA) [18]. In Japan, a nepherometric immunoassay that is specific for canine CRP was developed in 1998, and the data of canine plasma CRP concentrations were accumulated for more than 10 years [13].…”
mentioning
confidence: 99%
“…Details on recruitment procedure have been described elsewhere (Allenspach et al, 2004;Sauter et al, 2005Sauter et al, , 2006Spichiger et al, 2005). Animals were clinically examined and scored using the Canine Inflammatory Bowel Disease Activity Index (CIBDAI) (Jergens et al, 2003b) to define the severity of disease. A scoring from 0 to 3 indicates clinically insignificant disease, from 4 to 5 a mild degree of clinical symptoms, from 6-8 a moderate degree of clinical symptoms, and above 9 the scoring indicates a severe degree of clinical symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…In some instances, additional tests, such as trypsinlike immunoreactivity and serum assays for folate and cobalamin, were performed. Clinical disease activity was assessed by CIBDAI [6]. Briefly, 6 variables-attitude/activity, appetite, vomiting, stool consistency, stool frequency, and weight loss-were scored using a 4 point scale (0 to 3 points).…”
Section: Animalsmentioning
confidence: 99%
“…In dogs, the activity of IBD is normally assessed by pathological examination of biopsy specimens or calculation of the canine IBD activity index (CIBDAI) described by Jergens et al [6]. However, CIBDAI and pathological grading do not correlate with each other, and both indexes contain several subjective factors [1,12].…”
mentioning
confidence: 99%